2021
DOI: 10.1002/cepa.1331
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of fully encased composite columns under cyclic loads

Abstract: Concrete and steel have different advantages, concrete has high compression strength and low cost while steel has high tensile strength, rigidity and ductility. Composite members have other beneficial qualities beside all of them. Composite columns are used extensively in modern buildings essentially in industrial buildings. The main purpose of this study is an analysis and a comparison between the responses (load‐displacements) of different types of composite columns under cyclic loads. For this purpose, a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Considering several studies reported in the literature [12,[22][23][24][25][26][27][28][29], it was decided to choose the used finite element model Solid65, Solid185 and Link8 finite elements of the Ansys code [16]. The ANSYS code defined Solid65 as concrete in 3-D solid modelling with reinforcing bars for its ability to crack in tension and crush in compression.…”
Section: General Configuration Of the Composite Columns And Boundary Conditionsmentioning
confidence: 99%
“…Considering several studies reported in the literature [12,[22][23][24][25][26][27][28][29], it was decided to choose the used finite element model Solid65, Solid185 and Link8 finite elements of the Ansys code [16]. The ANSYS code defined Solid65 as concrete in 3-D solid modelling with reinforcing bars for its ability to crack in tension and crush in compression.…”
Section: General Configuration Of the Composite Columns And Boundary Conditionsmentioning
confidence: 99%